Apple launches a crack in the book world - García-Marco, Francisco-Javier (Anuario ThinkEPI, 2012)
The relevance and potential impact of Apple Computer´s iBooks initiative is discussed. iBooks is aimed at the USA textbook market, but it has a great potential to expand, as has previously occurred with other services that use iTunes, Apple´s B2C-C2C e-commerce and digital distribution platform. The initiative combines hardware, authoring software, e-reader, distribution channels, and social and networking services integration to empower systemically and synergistically its products and services against those of the competition, creating a new prototypic exemplar of the so-called "digital ecosystems".